Perception of the probability of Korean unification amongst South Korea’s elderly population - Szabo, Sylvia; Danaa, Samuel; Park, Geonwoo; Choi, Sangmi (Bulletin of Geography. Socio-economic Series, 2022)
While Korean unification remains one of the most significant issues in inter-Korean and international affairs, little is known about the perception of the likelihood of the Korean unification, especially amongst the elderly population. Yes, the proportion of the population in South Korea has been rapidly rising, becoming an increasingly important civic group. In this study, we analyzed the data from the 2018 nationally representative Korean Longitudinal Study of Aging survey using ordered logistic regression modelling. The results show that age, life satisfaction, health status, participation in social activities, and geographical location are the most important factors affecting the perception of Korean unification. We also find some gender differences in relation to the impact of education and wealth. Further qualitative studies might be useful to gain an in-depth understanding of people’s perceptions as well as possible socioeconomic and cultural barriers to a potential pre-unifying process.